A systematic review and meta-analysis of the effect of routine early angiography in patients with return of spontaneous circulation after Out-of-Hospital Cardiac Arrest. (June 2021) - Nikolaou, Nikolaos I.; Netherton, Stuart; Welsford, Michelle; Drennan, Ian R.; Nation, Kevin; Belley-Cote, Emilie; Torabi, Nazi; Morrison, Laurie J.; ,; Belley-Cote, Emilie; Drennan, Ian; Welsford, Michelle; et al.
Abstract: Background: Early coronary angiography (CAG) has been reported in individual studies and systematic reviews to significantly improve outcomes of patients with return of spontaneous circulation (ROSC) after cardiac arrest (CA). Methods: We undertook a systematic review and meta-analysis to evaluate the impact of early CAG on key clinical outcomes in comatose patients after ROSC following out-of-hospital CA of presumed cardiac origin. We searched the PubMED, EMBASE, CINAHL, ERIC and Cochrane Central Register of Controlled Trials databases from 1990 until April 2020. Eligible studies compared patients undergoing early CAG to patients with late or no CAG. When randomized controlled trials (RCTs) existed for a specific outcome, we used their results to estimate the effect of the intervention. In the absence of randomized data, we used observational data. We excluded studies at high risk of bias according to the Robins-I tool from the meta-analysis. The GRADE system was used to assess certainty of evidence at an outcome level. Results: Of 3738 citations screened, 3 randomized trials and 41 observational studies were eligible for inclusion. Evidence certainty across all outcomes for the RCTs was assessed as low. Randomized data showed no benefit from early as opposed to late CAG across all critical outcomes of survival and survival with favourable neurologic outcome for undifferentiated patients and for patient subgroups without ST-segment-elevation on post ROSC ECG and shockable initial rhythm. Conclusion: These results do not support routine early CAG in undifferentiated comatose patients and patients without STE on post ROSC ECG after OHCA. Review registration: PROSPERO — CRD42020160152.